Polymorphous Low-Grade Adenocarcinoma of the Tongue Base Treated by Transoral Robotic Surgery - Jeong Hong Kim; Chang Lim Hyun; Gil Chai Lim (Case Reports in Otolaryngology)
Polymorphous low-grade adenocarcinoma is a rare malignancy arising from the minor salivary glands in the aerodigestive system, most frequently the hard palate. The treatment of choice is wide surgical resection, and the efficacy of radiotherapy has not been confirmed. A 54-year-old male presenting with a mass at the base of the tongue performed transoral laser microsurgery. The pathologic diagnosis was polymorphous low-grade adenocarcinoma. Complete surgical excision was performed via transoral robotic surgery without a flap reconstruction of the surgical defect. Without complications of bleeding or injury to the hypoglossal nerve, proper surgical margins were obtained, and no recurrence was found after 6 months after surgery. The patient did not complain of dysphagia or aspiration. We conclude that, in surgery for tongue base tumors with unknown malignant potential, transoral robotic surgery can be considered for achieving a definite resection avoiding a mandibulotomy without complications of dysphagia or aspiration after confirmation of malignancy with a frozen biopsy.